Optimal Multi-Distributed Generators Planning Under Uncertainty using AHP and GA - Wanxing Sheng; Limei Zhang; Wei Tang; Jinli Wang; Hengfu Fang (Institute of Advanced Engineering and Science, 2014)
Power system deregulation and the shortage of energy sources have led to increased interests in distributed generators (DGs). The access of DGs to the distribution networks brings advantages as well as creates adverse influences, which is related to the type, location and size of DGs. In order to fully apply the positive and restrain the negative, proper DGs planning is very important and indispensable. Based on the analysis of the uncertain factors, this paper presents the distribution features of load, WTG and PV. And According to these distribution features, the relatively accurate sampling data are obtained by different discretization methods. Furthermore, this paper also presents an uncertain planning model of DGs owned by the distribution company, which involve power loss improvement, the system voltage quality variation, environment change, etc. The optimization algorithm is based on the fusion methodology with the Monte Carlo simulation, the analytical hierarchy process (AHP) and genetic algorithm (GA). The simulation is carried out on IEEE 37-bus distribution systems and the results is presented and discussed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4824